2002
DOI: 10.1016/s0735-1097(02)02158-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of serotonin in ischemic cellular damage and the infarct size-reducing effect of sarpogrelate, a 5-hydroxytryptamine-2 receptor blocker, in rabbit hearts

Abstract: Sarpogrelate reduces the myocardial infarct size by inhibiting the serotonin release followed by enhancement of PKC-epsilon translocation and opening of the mitochondrial KATP channel in ischemic myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 17 publications
3
65
0
2
Order By: Relevance
“…Various favorable cardiovascular pleiotropic actions of sarpogrelate have been reported. [1][2][3][4][5] A recent preliminary study by Yamakawa et al 14 showed a chronic increase in circulatory adiponectin and reduced HOMA-R in a small number of patients with treated diabetes mellitus (n=8) following sarpogrelate administration. Considering the wide range of actions of adiponectin on ASCDs, [13][14][15][16][17][18] sarpogrelate might have a beneficial effect on risk factor control and secondary prevention of ASCDs.…”
Section: Discussionmentioning
confidence: 99%
“…Various favorable cardiovascular pleiotropic actions of sarpogrelate have been reported. [1][2][3][4][5] A recent preliminary study by Yamakawa et al 14 showed a chronic increase in circulatory adiponectin and reduced HOMA-R in a small number of patients with treated diabetes mellitus (n=8) following sarpogrelate administration. Considering the wide range of actions of adiponectin on ASCDs, [13][14][15][16][17][18] sarpogrelate might have a beneficial effect on risk factor control and secondary prevention of ASCDs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported the infarct-size reducing effect of sarpogrelate in rabbit hearts without collateral flow. 10 That effect was completely blocked by a selective PKC inhibitor, chelerythrine, and a mitochondrial KATP channel blocker, 5-hydroxydecanoate, suggesting that the mechanism was related to translocation of PKC followed by opening of a mitochondrial KATP channel, which is the same mechanism as IPC. 10 In addition, it has been shown that serotonin (5HT) is released from cardiac cells, such as from platelets in the vascular beds, mast cells and sympathetic nerve endings, within the area at risk during ischemia.…”
Section: Mechanism Of the Protective Effect Of Sarpogrelatementioning
confidence: 96%
“…10 That effect was completely blocked by a selective PKC inhibitor, chelerythrine, and a mitochondrial KATP channel blocker, 5-hydroxydecanoate, suggesting that the mechanism was related to translocation of PKC followed by opening of a mitochondrial KATP channel, which is the same mechanism as IPC. 10 In addition, it has been shown that serotonin (5HT) is released from cardiac cells, such as from platelets in the vascular beds, mast cells and sympathetic nerve endings, within the area at risk during ischemia. 10 The increase in myocardial interstitial serotonin induces the release of a large amount of serotonin from aggregated platelets via their 5-HT2A receptors.…”
Section: Mechanism Of the Protective Effect Of Sarpogrelatementioning
confidence: 96%
See 1 more Smart Citation
“…5-HT levels are drastically increased during myocardial ischemia, and blockade of the 5-HT 2 receptor improves the outcome after myocardial infarction in different mouse models [52,53].…”
Section: Vikenes Et Al Detected a 10-fold Increase Of Plasma 5-ht Inmentioning
confidence: 99%